Estimated contribution of hemoglobin and myoglobin to near infrared spectroscopy - Davis, Michelle L. (Kansas State University, 2009)
Near infrared spectroscopy is currently routinely used to assess tissue (muscle) oxygenation at rest and during exercise. While most investigators assume that hemoglobin ([Hb]) is the major contributor to the responses seen during exercise, the relative contribution of myoglobin ([Mb]) to the NIRS signals remains controversial. PURPOSE: a) To calculate the range of light absorbing potential (LAP) of hemoglobin and myoglobin in mammalian skeletal muscle at rest based on analysis of published chemical and morphometric data in humans and other mammals (Part 1), and b) use the information in a) to interpret changes in total [Hb+Mb] from NIRS during exercise (Part 2). METHODS: Part 1: Information was retrieved from five published studies with regard to capillary density (#caps/mm2) and [Mb] in skeletal muscle of human, horse and rat. Preference was given to studies in which both measurements were provided for the same muscles. [Hb] in skeletal muscle was estimated as a function of capillary density, [Hb] in systemic blood, and the ratio of capillary-to-systemic hematocrit at rest and during exercise. Part 2: Changes in total [Hb] + [Mb] (as t[Hb+Mb]) from published NIRS data obtained from human subjects performing cycling or knee extension exercise were interpreted in the context of the results of Part 1. RESULTS: Part 1: Individual group mean values for skeletal muscle [Mb] in the literature ranged from 0.25-0.67 mM in human samples, with a similar range for muscles of the rat hindlimb; horse limb muscles tended to be higher (up to 1.0 mM). Capillary densities ranged from ~200 to 600 caps/mm2 in human and rat muscles, and up to 800 caps/mm2 in horse muscle. Assuming a resting capillary hematocrit of 22% and 4 fold greater LAP for each mole [Hb] vs [Mb], the resulting estimation of capillary [Hb] ranged from ~0.03 to 0.09 mM in human and rat muscles, and up to ~0.13 mM in horse muscles. The results suggest that [Mb] could contribute ~50-70% of the total LAP at rest in human skeletal muscle. Part 2: With exercise, total heme by NIRS can increase ≥ 30% in individual human subjects. Assuming this increase reflects only increased [Hb], this fits well with the observed increase in capillary hematocrit with exercise. CONCLUSIONS: 1) In skeletal muscle at rest, [Mb] is likely to be at least as significant a light absorbing heme as is [Hb] in most mammalian muscles, including the human leg. 2) Observed increases in t[Hb+Mb] with NIRS during exercise can be explained by an increase in capillary hematocrit, even in the presence of significant [Mb].
Keywords: near infrared spectroscopy; myoglobin; hemoglobin; skeletal muscle; Health Sciences, General (0566)